Experimental proof of the shape constancy for isoenergetic ellipsoids in n–Ge under strong uniaxial elastic deformation - Gaidar, G.P.; Baranskii, P. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The experimental proof of the fact that, under a strong uniaxial elastic deformation of n−Ge samples, the isoenergetic ellipsoids are displaced only relatively on the energy scale, whereas the shape of ellipsoids remains unchanged, is obtained.